EU cohesion policy. Some fundamental questions - Indhira Santos (Bruegel, 2009)
Indhira Santos analyses the impact of the European Union`s cohesion policy both in terms of economic efficiency and redistribution to needy areas of the EU. She illustrates with data the confusion created by the multiple objectives of current EU cohesion policy and by the political horse-trading over levels of aid granted to different member states and regions. Finally, sh shows how a significant part of EU structural funds involves ine net economic terms simply transferring funds between individuals within one and the same region.
Keywords: 330; EU-Regionalfonds; EU-Strukturfonds; EU-Staaten